Testing and Assessment - Buško, Vesna (2011)
The first part of this article introduces *general overviews* and *textbooks* representing major aspects of testing theory, methodological principles in test design and evaluation, and the areas of application. Selected *reference works* concern either theoretical foundations of psychological testing, or the assessment issues used related to particular fundamental or applied fields of psychology. Several excellent *journals* that specialize in publishing articles on advances in psychometrics, along with theoretical and practical aspects of assessment, are also presented, as well as critical sources of information on measurement instruments and their utility. The article concludes with considerations of *ethical and social issues* that are linked to the process of psychological testing and assessment, including the responsibilities of all parties involved in the assessment data gathering procedures and the uses of test results.
Projekt MZOS
ENG